2001
DOI: 10.1103/physreve.63.021701
|View full text |Cite
|
Sign up to set email alerts
|

Hidden photoalignment of liquid crystals in the isotropic phase

Abstract: We found the effect of a hidden photoalignment of a dye-doped nematic liquid crystal (LC) on a nonphotosensitive polymer surface after polarized irradiation of the cell in the isotropic phase. We observed that irradiation resulted in a uniform planar orientation of the LC after cooling to the mesophase. The direction of a light-induced easy axis on the polymer can be either parallel or perpendicular to the polarization of the incident light, depending on the light intensity. We attribute this behavior to two m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 11 publications
2
54
0
Order By: Relevance
“…In fact the efficiency of adsorption or desorption is strongly dependent on incident light polarization. 4,5 In particular in our experimental arrangement, the pump light was polarised parallel to the initial cell orientation, which favours light absorption by MR molecules followed by desorption from the irradiated surface and subsequent adsorption from the bulk. On the contrary, if the incident light is polarised orthogonal to the initial easy axis, as in Fig.…”
Section: à áKmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact the efficiency of adsorption or desorption is strongly dependent on incident light polarization. 4,5 In particular in our experimental arrangement, the pump light was polarised parallel to the initial cell orientation, which favours light absorption by MR molecules followed by desorption from the irradiated surface and subsequent adsorption from the bulk. On the contrary, if the incident light is polarised orthogonal to the initial easy axis, as in Fig.…”
Section: à áKmentioning
confidence: 99%
“…These include enhancement of nonlinear optical response, 1,2 light-induced phototransformations, 2 photo-alignment techniques, [3][4][5][6] optical memory effects, 7,8 and optical processing methods. 9 A system widely studied is the mixture of the nematic pentyl-cyanobiphenil and the azo-dye Methyl Red (5CB þ MR) in weight concentration typically between 0.1 and 1%.…”
Section: Introductionmentioning
confidence: 99%
“…The authors also suggested that the absorption dichroism of LC molecules caused the anisotropic desorption of these molecules from the surface, making the adsorbed layer anisotropic with the long molecular axis perpendicular to the direction of polarization. Ouskova et al [40,41] showed that photoalignment of LCs in an MR-doped LC system depends strongly on the intensity of the pumping beam. They attributed the photoalignment effect to two mechanisms-adsorption and desorption, which dominate in strong-and weak-intensity regimes, respectively.…”
Section: Bulk-mediated Photo-isomerization and Adsorption Effectsmentioning
confidence: 99%
“…When the dye contains the azo-group, the photoinduced reversible conformational transformations are very promising for reversible optical memories or photochemical switching operations. There are also many studies which investigate the phenomena occurring in such systems [8][9][10][11][12][13]. Most of these studies are focused on molecular reorientation produced by electrical or optical fields.…”
Section: Introductionmentioning
confidence: 99%